The utility of a care model to individualize rehabilitation for critically ill patients: A scoping review - Adesulistyawati Adesulistyawati; Suhartini Ismail; Meira Erawati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Individualized care in intensive care units (ICUs) refers to holistic nursing care provided to critically ill patients, which takes into account their clinical conditions, personal life circumstances, and encourages their active involvement in the decision-making process.  Purpose: To synthesize the impact of individualized care on the rehabilitation outcomes of critically ill patients. Method: A scoping review approach was employed. The literature search was conducted using PubMed, ScienceDirect, and EBSCO databases, utilizing a keyword strategy with Boolean operators "OR" and "AND" combining the terms: Individualized care and Rehabilitation. Results: The review revealed cross-country differences in nurses’ perceptions of individualized care. Nurses from Nordic countries and the United States generally rated the Individualized Care Scale–Nurse (ICS-Nurse) variables more highly, whereas nurses from Mediterranean and Southern European countries tended to provide lower ratings. Conclusion: Overall, nurses are committed to supporting patient individuality through comprehensive nursing practices, although certain barriers persist. It is recommended that nurses more consistently integrate patients’ personal life contexts into their care to enhance individualized care delivery.